Intelligent heterogeneous wireless network using machine learning techniques - Ko, Sandra Shi Hui (Nanyang Technological University, 2022)
This project presents a passive monitoring system designed to identify a good channel using machine learning that operates on a standalone basis. The measurements required can be acquired using standard hardware and being a passive monitoring system, does not disrupt the network. The appropriate channels can then be allocated to the devices in the heterogenous network.